The Effects of Arterial Blood Pressure Reduction on Endocan and Soluble Endothelial Cell Adhesion Molecules (CAMs) and CAMs Ligands Expression in Hypertensive Patients on Ca-Channel Blocker Therapy - Refmir Tadzic; Martina Mihalj; Aleksandar Vcev; Johann Ennen; Arijan Tadzic; Ines Drenjancevic-Peric (Karger Publishers, 2013)
Background/Aims: To determine the effect of arterial blood pressure (BP) reduction on endocan and soluble cell adhesion molecules' (sCAM) plasma concentration and expression of their ligands on circulatory leukocyte subpopulations. Methods: 24 hypertensive subjects of both sexes (age: 53±8 yrs) were treated with Ca-channel blocker, amlodipin (5-10 mg/day for 8 weeks; to reach BP≤139/89mmHg). The serum sCAMs and endocan concentrations were determined by ELISA kits. Level of ICAM/VCAM ligands on leukocytes was assessed by flow cytometry. Paired t-test, or t-test were used as appropriate, with Pearson's correlation calculated; pResults: sICAM-1 and sVCAM-1 were decreased (p≤0.001 and p=0.002, respectively), while E-selectin concentration was increased after amlodipin treatment (P=0.014). CD11a/LFA-1 (ICAM-1 and endocan ligand) was significantly increased in all three cell types with BP decrease. CD15 and CD49d/VLA-4 (VCAM-1 ligand) did not change after the treatment. There was significant positive correlation of systolic and diastolic BP with ICAM-1 and VCAM-1, and significant negative correlation of systolic BP with CD11a/LFA-1. Endocan significantly positively correlated with ICAM-1. Conclusions: The increased expression of ICAM/VACM ligands, together with decrease of sCAMs and endocan suggests the de-activation of endothelium with reduction in BP, decreasing the adherence of circulatory leukocytes to endothelium; subsequently decreasing the risk for development of atherosclerosis.